Differential Responsiveness to BMP9 between Patent and Fused Suture Progenitor Cells from Craniosynostosis Patients. Issue 3 (March 2020) - Song, Dongzhe; Huang, Shifeng; Zhang, Linghuan; Liu, Wei; Huang, Bo; Feng, Yixiao; Liu, Bo; He, Tong-Chuan; Huang, Dingming; Reid, Russell R.
Abstract : Background: Several studies have verified that bone morphogenetic proteins (BMPs) may be involved in the development of craniosynostosis; little attention has been focused on the role of BMP9 in cranial suture biology. The authors investigated the role of BMP9 in suture progenitor cells. Methods: The authors isolated and cultured prematurely fused and internal control patent suture progenitor cells from patients with nonsyndromic craniosynostosis. Overexpression of BMP9 was mediated by adenoviral vectors. Osteoblast and osteoclast differentiation-related markers were evaluated by staining techniques and touchdown quantitative polymerase chain reaction analysis. In vivo analysis of BMP9-induced suture progenitor cell osteogenesis was performed in an ectopic bone formation model. Results: The authors demonstrated that the prematurely fused sutures have a higher endogenous expression of the osteogenic differentiation-related genes than patent sutures, whereas the same pattern of gene expression exists between fused and patent suture progenitor cells. Importantly, both patent and fused suture progenitor cells undergo osteogenic differentiation and express multiple lineage regulators and NELL-1 on BMP9 stimulation, whereas fused suture progenitor cells have a higher basal osteogenic potential than patent suture progenitor cells. BMP9 regulates the expression of osteoclast differentiation-related genes in suture progenitor cells. Forced BMP9 expression enhances the mineralization and maturity of ectopic bone formation of suture progenitor cells implanted in vivo. Conclusions: The authors' findings suggest that fused suture progenitor cells have elevated osteogenic potential. BMP9 could regulate the expression of multiple osteoblast and osteoclast differentiation-related genes, and NELL-1, in both suture progenitor cells, indicating that BMP9 may play a role in craniosynostosis. Abstract : Supplemental Digital Content is available in the text.